Investigating the Link between Eating Attitudes, Taste and Odour Preferences and the Chemical Senses - Layla St Clair; Alyssa Grady; Mehmet K. Mahmut (Biology, 2023)
Objectives: To examine if higher degrees of pathological eating attitudes in a non-clinical sample are associated with odour and taste perception and preferences based on psychophysical ratings. Participants and Methods: A total of 80 female university students completed the eating attitudes test (EAT-26), followed by four chemosensory measures including olfactory and gustatory perception plus perceptual ratings and preferences for food odours and tastes. Results: There were no significant correlations between EAT-26 scores and measures of olfactory and gustatory perception. However, a significant interaction effect indicated higher degrees of pathological eating attitudes may be associated with differential sensitivity to sweet and fatty food odours compared to those with lower levels of pathological eating attitudes. Conclusions: This was the first study to examine pathological eating attitudes using food stimuli with a non-clinical sample. The results remain preliminary until replication. However, the findings highlight the need for development of measures of disordered eating attitudes and behaviours that go beyond caloric restriction.